Working With Subgroup Identities to Build Organizational Identification and Support for Organizational Strategy: A Test of the ASPIRe Model. (February 2013) - Peters, Kim; Haslam, S. Alexander; Ryan, Michelle K.; Fonseca, Miguel
A growing body of evidence indicates that organizational identification underpins a range of important organizational outcomes. However, to date, the literature has provided little empirically grounded guidance for organizations that are trying to develop organizational identification among their employees. In this article, the authors aim to address this lacuna by testing the effectiveness of the ASPIRe ( A ctualizing S ocial and P ersonal I dentity Re sources) model—a model that specifies a sequence of structured activities designed to use subgroup identities as a platform for building organizational identification—in a bespoke workshop delivered to senior military health services personnel. As predicted by the ASPIRe model, participants reported increased levels of subgroup and organizational identification as a result of the workshop and were also more supportive of the organization's strategy.